2015
DOI: 10.4236/ajps.2015.64058
|View full text |Cite
|
Sign up to set email alerts
|

Field Efficacy of Chemical Pesticides against Maruca vitrata Fabricius (Lepidoptera: Crambidae) Infesting Soybean in Brazil

Abstract: The soybean pod borer, Maruca vitrata, can cause great damage by attacking pods from soybean plants. The aim of this study was to evaluate the field efficacy of chemical pesticides, when applied in spray, against soybean pod borer. The experiment was conducted in the experimental area of Fundação, MS, in Maracaju, MS, Brazil, in the growing season 2012/2013. The randomized block design was used with six treatments (teflubenzuron, flubendiamide, methomyl, chlorantraniliprole + lambda-cyhalothrin, chlorpyrifos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…Swamy et al (2010) found that Flubendiamide provided good protection and less pod damage among newer insecticides viz., Flubendiamide, Spinosad, and Emamectin benzoate. Grigolli et al (2015) also observed the similar findings in context to management of Maruca vitrata through Flubendiamide in soyabean. Sreekanth and Maha Lakshmi (2012) reported that the percent inflorescence damage due to legume pod borer is the lowest in Spinosad 45% SC @ 73 g a.i/ha treated plots (4.74%) followed by Bacillus thuringiensis @ 1.5 kg/ha (10.52 %) ISSN: 2661-6270 (Print), ISSN: 2661-6289 (Online) DOI: https://doi.org/10.3126/janr.v4i1.33250 which is highest in control (24.79%) in pigeonpea.…”
Section: Resultssupporting
confidence: 79%
“…Swamy et al (2010) found that Flubendiamide provided good protection and less pod damage among newer insecticides viz., Flubendiamide, Spinosad, and Emamectin benzoate. Grigolli et al (2015) also observed the similar findings in context to management of Maruca vitrata through Flubendiamide in soyabean. Sreekanth and Maha Lakshmi (2012) reported that the percent inflorescence damage due to legume pod borer is the lowest in Spinosad 45% SC @ 73 g a.i/ha treated plots (4.74%) followed by Bacillus thuringiensis @ 1.5 kg/ha (10.52 %) ISSN: 2661-6270 (Print), ISSN: 2661-6289 (Online) DOI: https://doi.org/10.3126/janr.v4i1.33250 which is highest in control (24.79%) in pigeonpea.…”
Section: Resultssupporting
confidence: 79%
“…Grain yield losses of 50%-71% were reported in pigeon pea and Adzuki bean (Sharma & Franzmann, 2000). In Brazil, M. vitrata is considered as a seasonal pest on soybean (Hoffmann-Campo et al, 2000), and it caused about 56% damage (Grigolli, Lourenção, & Ávila, 2015). Up to 380,000 t of cowpea was lost due to M. vitrata in Malawi, Senegal, Niger, Tanzania, and Kenya (Gressel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Up to 380,000 t of cowpea was lost due to M. vitrata in Malawi, Senegal, Niger, Tanzania, and Kenya (Gressel et al, 2004). In Brazil, M. vitrata is considered as a seasonal pest on soybean (Hoffmann-Campo et al, 2000), and it caused about 56% damage (Grigolli, Lourenção, & Ávila, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The major destructive pest on mungbean namely Maruca sp., feed on flowers, buds, and pods by webbing them [17]. Tight webbing produced by larva of Maruca sp.…”
Section: Discussionmentioning
confidence: 99%